2016
DOI: 10.1002/hipo.22561
|View full text |Cite
|
Sign up to set email alerts
|

Tests of pattern separation and pattern completion in humans—A systematic review

Abstract: Objective: To systematically review the characteristics, validity and outcome measures of tasks that have been described in the literature as assessing pattern separation and pattern completion in humans.Methods: Electronic databases were searched for articles. Parameters for task validity were obtained from two reviews that described optimal task design factors to evaluate pattern separation and pattern completion processes. These were that pattern separation should be tested during an encoding task using abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 88 publications
(146 reference statements)
2
47
0
Order By: Relevance
“…It is notable that all of the aforementioned studies reported that SenseCam photographs led patients to recall event details that were not themselves apparent in the images. This suggests that these automatically captured first‐person snapshots might be particularly effective at triggering mnemonic pattern‐completion processes, perhaps by harnessing the functional contribution of any intact portions of the patients’ hippocampi to bring associated event details back to mind. Indeed, Loveday and Conway reported that their amnesic patient would occasionally experience a “Proustian moment”—a powerful flood of recollected details—when encountering her SenseCam photographs.…”
Section: Research In Clinical Contextsmentioning
confidence: 99%
“…It is notable that all of the aforementioned studies reported that SenseCam photographs led patients to recall event details that were not themselves apparent in the images. This suggests that these automatically captured first‐person snapshots might be particularly effective at triggering mnemonic pattern‐completion processes, perhaps by harnessing the functional contribution of any intact portions of the patients’ hippocampi to bring associated event details back to mind. Indeed, Loveday and Conway reported that their amnesic patient would occasionally experience a “Proustian moment”—a powerful flood of recollected details—when encountering her SenseCam photographs.…”
Section: Research In Clinical Contextsmentioning
confidence: 99%
“…Notably, this deficit is apparent in tests of pattern separation unrelated to the particular trauma: humans diagnosed with PTSD or related anxiety disorders perform poorly on neuropsychological tests of pattern separation 22 . By contrast, some humans diagnosed with autism spectrum disorder have enhanced pattern separation and note even slight differences in contexts or routines 110 . In PTSD, the severity of symptoms is correlated with a smaller and less active DG, as compared to healthy controls.…”
Section: Pattern Separationmentioning
confidence: 99%
“…The hippocampus is necessary for recollection because of its unique ability to assign independent representations to even highly similar stimuli (Lacy, Yassa, Stark, Muftuler, & Stark, 2011; through processes known as pattern separation and pattern completion. Our experimental design was however not meant to test for pattern separation (see Liu, Gould, Coulson, Ward, & Howard, 2016) and the resolution of our fMRI data would not allow for correlational multi-voxel pattern analyses across subfields of the hippocampus, believed to have distinct contributions to pattern separation/completion (e.g. .…”
Section: Introductionmentioning
confidence: 99%